2004
DOI: 10.1080/14017430410028500
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery blood temperature at admission to the intensive care unit is predictive of outcome after on‐pump coronary artery bypass surgery

Abstract: Patients having a PA temperature > or =36.4 degrees C at admission to the ICU after CABG seem to be at higher risk of poor postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In our ten years of experience, delayed hypothermia called our attention in patients who required re-exploration because of bleeding where its source could not be identified. A study performed by Lahtinen et al encouraged us to do this study as the authors reported a correlation between volume of postoperative bleeding and low pulmonary artery temperatures [5]. Nathan et al reported that the depth of hypothermia is an important parameter for postoperative bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…In our ten years of experience, delayed hypothermia called our attention in patients who required re-exploration because of bleeding where its source could not be identified. A study performed by Lahtinen et al encouraged us to do this study as the authors reported a correlation between volume of postoperative bleeding and low pulmonary artery temperatures [5]. Nathan et al reported that the depth of hypothermia is an important parameter for postoperative bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results may be attributable to the fact that the previous studies only used a single measurement of temperature upon arrival at the ICU and that patient management was not according to a standardized protocol 10,11,28. In addition, a recent study involving the largest cohort of cardiac surgical patients depicted that transient hypothermia was not associated with adverse outcome 29.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the temporal continuity, intraoperative temperatures essentially influence the temperature upon ICU arrival, and only the latter had been validated in most of the previous studies 10,11,28. Postoperative persistent hypothermia may affect bleeding as well, however, it was not possible to address this relationship, as all of the patients were normothermic within 2 hr after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Lahtinen et al encouraged us to do this study as the authors reported a correlation between volume of postoperative bleeding and low pulmonary artery temperatures [5]. Nathan et al reported that the depth of hypothermia is an important parameter for postoperative bleeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…We can not say this definitively as many reasons, such as low cardiac output, can cause coagulation deficits [5]. We did not measure the cardiac output as this is not routine in our service and thus was not recorded on patients' records and this is a retrospective study.…”
Section: Discussionmentioning
confidence: 99%